TOI-4504 : exceptionally large transit timing variations induced by two resonant warm gas giants in a three-planet system - Vítková, Michaela; Brahm, Rafael; Trifonov, Trifon; Kabáth, Petr; Jordán, Andrés; Henning, Thomas; Hobson, Melissa J.; Eberhardt, Jan; Pinto, Marcelo Tala; Rojas, Felipe I.; Espinoza, Nestor; Schlecker, Martin; et al. (The astrophysical journal. Part 2, Letters, 2025)
We present a joint analysis of transit timing variations (TTVs) and Doppler data for the transiting exoplanet system TOI-4504. TOI-4504 c is a warm Jupiter-mass planet that exhibits the largest known TTVs, with a peak-to-node amplitude of ∼2 days, the largest value ever observed, and a superperiod of 930 days. TOI-4504 b and c were identified in public Transiting Exoplanet Survey Satellite (TESS) data, while the TTVs observed in TOI-4504 c, together with radial velocity (RV) data collected with FEROS, allowed us to uncover a third, nontransiting planet in this system, TOI-4504 d. We were able to detect transits of TOI-4504 b in the TESS data with a period of 2.4261 ± 0.0001 days and derive a radius of 2.69 ± 0.19 R⊕. The RV scatter of TOI-4504 was too large to constrain the mass of TOI-4504 b, but the RV signals of TOI-4504 c and d were sufficiently large to measure their masses. The TTV+RV dynamical model we apply confirms TOI-4504 c as a warm Jupiter planet with an osculating period of 82.54 ± 0.02 days, a mass of 3.77 ± 0.18 MJ, and a radius of 0.99 ± 0.05 RJ, while the nontransiting planet TOI-4504 d has an orbital period of 40.56 ± 0.04 days and a mass of 1.42 MJ. We present the discovery of a system with three exoplanets: a hot sub-Neptune and two warm Jupiter planets. The gas giant pair is stable and likely locked in a first-order 2:1 mean-motion resonance (MMR). The TOI-4504 system is an important addition to MMR pairs, whose increasing occurrence supports a smooth migration into a resonant configuration during the protoplanetary disk phase.
Gesehen am 23.10.2025